Sistem Web Inventaris: Optimalisasi Logistik dan Stok dari Gudang ke Toko Awanda - Lili Indah Sari; Wishnu Aribowo Probonegoro; Parlia Romadiana (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
Inventory of goods is an important work activity in a trading business. Improper inventory management can cause deviations in inventory control, errors in recording the entry and exit of goods, and even a decline in business performance. Awanda Shop is a shop that operates in the staple goods business. The process of entering and exiting goods from the warehouse to the shop still often occurs with errors, delays in delivery, stock imbalances with the availability of goods in the shop, because the recording is still done manually. The existence of this inventory problem made the author analyze and help create a web-based inventory information system to optimize logistics and stock control from the warehouse to the store, making it easier to check and control well. This research uses Rapid Application Development (RAD) with UML (Unified Modeling Language) to communicate designs in paper based form. The database design used is using ERD and LRS, the UML tools used by the author are activity diagrams and use case diagrams. Having a web-based inventory system can simplify the processing for users. transactions and distribution of inventory in warehouses and shops, prevent discrepancies in existing inventory, prevent fraud or loss of goods, increase efficiency and effectiveness of service and performance